Disintegration of the BRELL electric ring: causes and consequences for the Baltic states - Anatoly I. Bazhan (Научно-аналитический вестник Института Европы РАН)
The article discusses some problems of energy supply of the Baltic republics with electricity after their accession to the European Union. The policy of Brussels aimed at curtailing energy cooperation between the Baltic States and Russia and Belarus is analyzed. The calculations of the investment costs incurred by the Baltic countries as a result of disconnection from the Russian and Belarusian power grids and synchronization of electricity flows with the EU countries are given. Other negative consequences of this act for the Baltic region, which await it after leaving the BRELL electric ring, are shown. Such consequences include the instability of electricity supply to the population, enterprises and organizations in the region, as well as an increase in prices for consumed electricity.